P291 Effect of the preconception steroid-free remission period on disease activity during pregnancy and birth outcomes in women with Ulcerative Colitis: a retrospective cohort study. (21st January 2022) - Ikeda, A; Kunisaki, R; Aoki, S; Yaguchi, K; Asami, S; Furusawa, K; Atsusaka, R; Azuma, D; Tsunoda, S; Fujii, K; Nishida, D; Madarame, A; et al.
Abstract: Background: Current consensus statements recommend at least 3–6 months of preconception steroid-free remission for women with inflammatory bowel disease, as determined by experts. However, little data is available on the appropriate preconception remission period in women with ulcerative colitis (UC). We explored the effect of the preconception steroid-free remission period on disease activity during pregnancy and birth outcomes in women with UC. Methods: Data were obtained from a retrospective chart review of 141 consecutive pregnant women with UC at our inflammatory bowel disease centre and a related clinic from 2000–2020. Women who were diagnosed with UC more than 6 months before conception and who were judged to have been accurately assessed for disease activity during the 6-month preconception period and at each trimester during pregnancy were included. We categorized the women into four subgroups according to their preconception steroid-free remission periods (≥6 months, 3–6 months, <3 months, and active disease at conception) and compared the disease activity during pregnancy and adverse birth outcomes in the four subgroups. Multivariable logistic regression of risk factors of disease activity during pregnancy and adverse birth outcomes was performed. Results: The rate of active disease during pregnancy was 63% in the ≥6 months preconception steroid-free remission group, 50% in the 3–6 months preconception steroid-free remission group, 71% in the <3 months preconception steroid-free remission group, and 93% in the active disease at conception group. The rates of active disease during pregnancy were significantly lower in all the preconception steroid-free remission groups than in the active disease at conception group. In the multivariate analysis, independent predictors of disease activity during pregnancy were a preconception steroid-free remission period of ≥6 months [adjusted odds ratio (aOR), 0.13; p <0.001], 3–6 months (aOR, 0.09; p <0.001), and <3 months (aOR, 0.17; p <0.05) compared with active disease at conception after adjustment for age and smoking. Active disease at conception was also an independent predictor of disease activity during pregnancy (aOR, 8.13; p <0.001) compared with remission at conception. The neonatal birthweight tended to decrease as the length of preconception steroid-free remission period decreased. Preterm birth, low birth weight, and small for gestational age were more common in the <3 months and active disease at conception groups ( p >0.05). Conclusion: The largest risk factor for disease activity during pregnancy appears to be active disease at conception. A shorter preconception steroid-free remission period than the recommended 3–6 months might reduce the risk of disease activity during pregnancy.